Novel axial flux machines topology assessment and their feasible applications - Kalpana Anumala; Ramesh Babu Veligatla (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The axial flux machines (AFMs) which got discovered long back in 1821 were shelved out due to their manufacturing complexities. These machines are now reconsidered as novel topologies as their topology is well suitable for fulfilling the present day technical and societal needs. An attempt has been made in this paper to assess the different structures of Axial Flux Machines and to identify the feasible applications. The advantages of AFMs have been highlighted in wind energy conversion systems and electrical vehicle applications. An exhaustive comparison has been carried out in this work between the conventional radial flux and axial flux machines through their sizing equations.